Minimum Quality Standards and Exports - Jan Voßwinkel; Laura Birg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the interaction of a minimum quality standard and exports in a vertical product differentiation model when firms sell global products. If ex ante quality of foreign firms is lower (higher) than the quality of exporting firms, a mild minimum quality standard in the home market hinders (supports) exports. The minimum quality standard increases quality in both markets. A welfare maximizing minimum quality standard is always lower under trade than under autarky. A minimum quality standard reduces profits for the exporting firm. It increases domestic welfare, but reduces welfare in the export market.
Keywords: F12; L13; L50; 330